Can Cell-type specific variability be involved in a rare variant of Unverricht-Lundborg? Investigation with iPSC generated models - Duarte, Ana Joana (2021)
Homozygosity for a private synonymous mutation in the cystatin-B gene (CSTB, MIM:601145; c.66G>A; p.Q22Q) was detected in a Portuguese patient with a rare, atypical form of Unverricht-Lundborg disease (ULD, MIM #254800). This apparently silent mutation leads to mis-splicing of CSTB pre-mRNA where a normal and an abnormal transcript were detected. Using iPSCs as a source of different cell types, we intend to clarify if the observed abnormal RNA splicing is cell-type specific, and to characterise the subsequent protein mislocalization. In conclusion, we hope to be able to contribute to the understanding of cell-type specific implications in the pathogenesis of ULD.